A roasting mixture and its application
By preparing a calcined mixture of specific lithium-containing raw ore materials, the problems of low lithium grade, complex composition and high impurity precipitation rate in the existing lithium electrode sheet material extraction process are solved, and the effects of high lithium leaching rate and low impurity precipitation rate are achieved, which are suitable for large-scale deep lithium extraction.
Patent Information
- Application Number
- CN202311512270.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-11-14
AI Technical Summary
In the existing lithium electrode sheet material lithium extraction process, the ore has low lithium grade, complex composition and large miscellaneous content, which makes it difficult to guarantee the yield and purity of lithium extraction on industrial scale. Although the lithium leaching rate is increased after the introduction of the roasting additive, it also leads to high impurity ion precipitation rate and low overall recovery rate.
By preparing a specific calcination mixture, the mixture contains the target elements lithium, aluminum and silicon in the lithium-containing raw ore material, and defines the content ratio of the calcination assisting element, so that it has high lithium leaching efficiency and low impurity ion precipitation after calcination.
It realizes high selective precipitation of lithium elements during industrial lithium extraction, improves lithium leaching rate and comprehensive recovery rate, and reduces the precipitation rate of impurity ions, which is suitable for deep lithium extraction of large batches of ore-containing raw materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of metallurgy, and in particular to a roasting mixture and application thereof. Background Art
[0002] With the continuous improvement of my country's industrialization technology and the continuous improvement of people's quality of life, the corresponding energy demand is gradually increasing. Compared with traditional petroleum energy, the demand for lithium battery energy is not proportional to the supply. In addition to the technical difficulties in the production of finished products, there are also technical bottlenecks in the raw material end of lithium battery energy.
[0003] At present, most lithium sources used in the preparation of lithium electrode sheet materials are basically obtained by extracting lithium from ores. This method basically processes and calcines lithium-containing minerals such as lithium mica, spodumene, and lithium-containing mine waste, and then uses wet leaching to extract the lithium elements contained in them in the form of ions, and then further processes them into lithium sources.
[0004] However, this type of ore has a low lithium grade, complex composition, and a large amount of impurities. It is difficult to ensure the yield and purity of lithium extraction on an industrial scale using traditional processes, and the supply naturally cannot be improved. Therefore, people have studied the introduction of some roasting aids such as sodium sulfate during the calcination of the ore to convert the lithium in the ore, making it easier to precipitate during the lithium extraction process. This improved method also effectively improves the lithium leaching rate of the roasted material after calcination. However, the introduction of roasting aids also changes the conversion path of each component of the roasted material during roasting. Although the lithium leaching rate has increased, it also causes some other impurity components to be converted into soluble substances and precipitate (including soluble components in the raw material itself), and the leaching selectivity is low, resulting in an extremely low final comprehensive recovery rate.
[0005] On the other hand, in order to improve efficiency, the lithium extraction industry adopts segmented leaching for large batches of roasted materials to ensure that the lithium in large tonnage ores is fully recovered. However, after the initial leaching of the roasted materials, most of the lithium contained in the remaining filter residue exists as insoluble compounds, and the impurity ion content in the leachate is high after leaching with the more corrosive acid or alkali solution commonly used. Once the amount of lithium extracted is insufficient, the benefit of segmented lithium extraction may be lower than the cost of impurity removal. Therefore, how to achieve high selectivity of lithium precipitation in the entire lithium extraction leaching process has become a key issue in improving industrial productivity and saving industrial costs in the existing lithium extraction industry. Summary of the invention
[0006] Based on the defects of the prior art, the purpose of the present invention is to provide a roasted mixture for industrial lithium extraction. The mixture is based on the relationship between the target element lithium and the large content of aluminum and silicon elements and the physical property characteristics contained in the mineral-containing raw materials, and at the same time limits the content ratio of the roasting auxiliary elements in the mixture, so that the product has considerable lithium leaching efficiency when leached after roasting, and the degree of precipitation of impurity ions is low. Most importantly, the roasted material prepared by the product has high lithium ion selectivity after a primary leaching and a secondary leaching of the obtained filter residue, which is very suitable for deep lithium extraction operations of large quantities of mineral-containing raw materials.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A roasting mixture for industrial lithium extraction, comprising the following components in percentage by mass:
[0009] At least one of Ca, Sr and Ba 5-11%, at least one of Na and K 10-12%;
[0010] The components of the calcined mixture also include Li, Si and Al, and satisfy the following relationship:
[0011] 0.0550≤m(Li)·B / [m(Si)·b+m(Al)]≤0.0680;
[0012] Where m(Li) is the mass percentage of Li in the calcined mixture;
[0013] m(Si) is the mass percentage of Si in the calcined mixture;
[0014] m(Al) is the mass percentage of Al in the roasted mixture;
[0015] B is the specific surface area of the roasted mixture, in m 2 / g;
[0016] b is the bulk density of the roasted mixture, in g / cm 3 .
[0017] In lithium-containing raw ore materials, in addition to the target lithium compounds, the main components are silicon compounds and aluminum compounds (mostly oxides), and also contain some soluble impurities such as sodium, potassium, rubidium, and cesium compounds (the total content is generally much greater than lithium). In the prior art, this type of raw ore material is mostly prepared by roasting activation, sulfate method or pressure cooking method, among which roasting activation method has the highest cost performance and is therefore the most commonly used. However, during the roasting process, since the raw ore materials are easily melted to form a molten body, it is difficult to achieve full activation and ensure that lithium can be effectively precipitated after roasting activation. In order to improve the recovery rate of lithium, some roasting aids are introduced in the prior art, such as calcium sulfate, sodium sulfate, etc., which are compound roasting to inhibit the formation of the molten body. However, the inventors found in actual operation that, for raw ore materials with low lithium content, although the introduction of roasting aids can improve the precipitation rate of lithium, on the one hand, the introduction of soluble ions (such as sodium ions) makes the precipitation rate of impurity ions higher when lithium is extracted by leaching in the subsequent process, and additional means are needed to remove impurities from the leachate, and the leaching rate of impurity ions is at least 20%; on the other hand, although calcium sulfate and the like do not introduce soluble ions, they will transform into a complex with silicon dioxide, aluminum oxide, etc. in the raw ore materials during the roasting process, and the content and morphology of this complex will have a great influence on the extraction process. There is a direct correlation between the leaching of lithium ions and soluble impurities. If the ratio of these roasting aids introduced into the raw ore material before roasting is improper, or the treatment process is improper when the powder is mixed, it is easy to lead to the unfavorable result of low lithium leaching rate and high soluble impurity leaching rate when the mixture is roasted for lithium extraction. However, in the prior art, the feeding ratio and feeding method of the roasting mixture before roasting are only calculated by mass ratio, and the degree of mixing of simple materials in a dry mixer, without in-depth research. Many factories use the same feeding ratio and feeding method to obtain roasting mixtures, but the effects of lithium extraction after roasting are very different.
[0018] In addition, in the prior art, after the roasted activated material is leached by the common leaching method, some insoluble lithium still exists in the remaining filter residue. If the volume of a single batch is large, the loss of this part of lithium is also large. Therefore, some manufacturers start to perform secondary lithium extraction on the filter residue after leaching when extracting lithium from large-volume raw ore materials. In this process, the leaching intensity of the leaching agent is higher (for example, weak acid, weak base or even neutral conditions may be used for the first leaching, and stronger acid and base conditions are required for the second lithium extraction). At this time, although the lithium can be fully leached, relatively speaking, some impurities that were not originally precipitated will also be leached simultaneously, and also require additional treatment. Therefore, it is often the case that the economic benefits of implementing secondary lithium extraction are small or even cannot offset the processing costs.
[0019] In the technical solution of the present invention, the inventors focus on the roasting mixture before roasting from two aspects: first, the key elements that inhibit the melt during the roasting process need to be specifically defined. These elements include sodium, potassium, and at least one of calcium, strontium, and barium. If the content of these elements is insufficient, the effect of inhibiting the production of the melt is not ideal, and lithium cannot be converted into soluble compounds; if the content is too much or the ratio is improper, it will lead to a high precipitation rate of soluble impurities, or lithium will be converted into insoluble compounds, which will reduce the lithium leaching rate; on the other hand, silicon and aluminum elements are relatively high in the original ore materials and exist in the form of oxides, among which the content of silicon dioxide is relatively high, generally reaching more than 50wt%, and will react with the roasting Elements such as calcium in the additives are compounded to form substances such as feldspar, quartz, and anhydrite. The inventors have discovered for the first time through experiments that these two elements, the lithium element in the mixture, and the specific surface area and bulk density of the mixture have a great influence on the roasting effect, and unexpectedly found that when the roasting mixture is prepared in a mixed process, as long as the constructed relationship m(Li)·B / [m(Si)·b+m(Al)] is within the range of 0.0550 to 0.0680, the dispersion of silicon dioxide and aluminum oxide during the roasting process is optimal for the selective leaching of lithium ions, which can make soluble impurity ions tightly wrapped in the insoluble body under mild or non-mild conditions, and lithium ions can be effectively leached from the gaps of the insoluble body. When adding roasting aids and pre-treatment powders, only when the above two aspects are met at the same time, the roasting mixture obtained is activated and leached according to the current conventional roasting process, and the comprehensive lithium selective leaching rate is the highest.
[0020] In addition, in repeated experiments, the inventors found that although the ratios of lithium, silicon and aluminum elements in the existing lithium-containing ore are relatively certain, the influence of the specific surface area and loose density of the roasted mixture on the lithium extraction performance cannot be directly studied without considering the composition relationship of these elements. If the relationship is not followed, even if the same mixed raw materials and mixed processing technology are used, the resulting roasted mixture may not achieve the expected lithium extraction effect after roasting and activation. Therefore, several parameters in the relationship need to be studied simultaneously.
[0021] Preferably, the composition of the calcined mixture includes 0.5-2% Li;
[0022] More preferably, the composition of the calcined mixture includes 0.6-1% Li.
[0023] Preferably, the composition of the calcined mixture includes 16-20% Si.
[0024] Preferably, the composition of the calcined mixture includes 10-12% Al.
[0025] The existing lithium-containing raw materials, in addition to lithium mica, also include some materials such as spodumene and lithium-containing mine waste, which are also used in the lithium extraction industry. Although the components of each material are different, the inventors found after screening that the lithium content of these lithium-containing raw materials is different, but the difference range of the content ratio of silicon dioxide (the main distribution form of Si) and aluminum oxide (the main distribution form of Al) is not large. Therefore, the relationship parameters constructed after introducing the roasting aid according to the composition limit of the roasting mixture described in the present invention are still applicable, and the products prepared from the same raw material system that do not meet the range have lower impurity leaching rate and lithium comprehensive recovery rate.
[0026] It should be noted that the composition testing method of the roasted mixture of the present invention can use elemental analysis methods to conduct qualitative and quantitative analysis of each element. Specifically, it can be carried out with reference to the method of YST 509.1-2008 "Chemical analysis method of spodumene and lithium mica concentrate - Determination of lithium oxide, sodium oxide and potassium oxide content - Flame atomic absorption spectrometry".
[0027] In the roasted mixture described in the present invention, the lithium element exists almost in the form of lithium oxide. For the convenience of statistics, the mass percentage of Li in the roasted material can be calculated using lithium oxide. Similarly, Si mainly exists in the form of silicon dioxide. Therefore, those skilled in the art can also calculate the mass percentage of Si in the roasted material using silicon dioxide. For the roasted mixture product, in order to facilitate its application in industrial lithium extraction, it can also be directly expressed by the proportion of each element as described above. However, those skilled in the art should know that the actual ranges of the two measurement methods are consistent based on common knowledge.
[0028] More preferably, in the calcined mixture, the mass percentage of Li is in the range of any one or both of 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, and 1%.
[0029] More preferably, in the calcined mixture, the mass percentage of Si is in the range of any one or both of 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, and 20%.
[0030] More preferably, in the calcined mixture, the mass percentage of Al is in the range of any one or both of 10%, 10.2%, 10.5%, 10.8%, 11%, 11.2%, 11.5%, 11.8%, and 12%.
[0031] Preferably, the roasting mixture comprises the following components in percentage by weight:
[0032] At least one of Ca, Sr and Ba: 5-7.6%, Na: 0.1-4%, K: 6-11.9%.
[0033] In the prior art, when introducing roasting aids, people often only compound the raw ore materials and roasting aids according to a certain mass ratio, and do not study the composite mixture. According to the inventor's research, the current mainstream roasting aids include one or more of calcium salts, barium salts, potassium salts and sodium salts (mainly introduced in the form of sulfates), but these elements exist in the raw ore materials themselves, and the content is not low (for example, in lithium mica, the potassium content generally reaches more than 5%). These components will also work together with the added roasting aids to guide the phase change of the composite and inhibit the formation of the melt. Therefore, based on the differences in the composition of lithium-containing raw ore materials and the differences in the types of roasting aids introduced, it is difficult for the existing roasting material processing scheme to guarantee a uniform effect. The inventor studies the roasting mixture obtained by mixing the lithium-containing raw ore materials and the roasting aids before roasting, thereby limiting the content ratio of several key roasting aid elements, which can effectively improve the activation effect of the lithium element in the obtained roasting material, so that the lithium element has a higher leaching rate in a single extraction process.
[0034] Preferably, the specific surface area of the calcined mixture is 1.8 to 2.5 m 2 / g;
[0035] More preferably, the specific surface area of the calcined mixture is 1.8 m 2 / g, 1.85m 2 / g, 1.9m 2 / g, 1.95m 2 / g, 2.0m 2 / g, 2.05m 2 / g, 2.1m 2 / g, 2.15m 2 / g, 2.2m 2 / g, 2.25m 2 / g, 2.3m 2 / g, 2.35m 2 / g, 2.4m 2 / g, 2.5m 2 / g or both.
[0036] Preferably, the bulk density of the roasted mixture is 0.6 to 1 g / cm 3 ;
[0037] More preferably, the bulk density of the calcined mixture is 0.6 g / cm 3 , 0.62g / cm 3 , 0.64g / cm 3, 0.66g / cm 3 , 0.68g / cm 3 , 0.7g / cm 3 , 0.72g / cm 3 , 0.74g / cm 3 , 0.76g / cm 3 、0.78g / cm 3 , 0.8g / cm 3 , 0.82g / cm 3 、0.84g / cm 3 , 0.86g / cm 3 , 0.88g / cm 3 , 0.9g / cm 3 , 0.92g / cm 3 、0.94g / cm 3 , 0.96g / cm 3 、0.98g / cm 3 , 1g / cm 3 The range value of one or both of them.
[0038] It should be noted that the specific surface area of the roasted mixture of the present invention is determined by the multi-point BET method, which can be directly obtained by instrument detection. The specific surface area is the multi-point specific surface area of the roasted mixture; in the present invention, when testing the specific surface area diameter, the mesh number of the roasted material is -100 mesh, accounting for 80%. Specifically, the nitrogen adsorption and desorption method is used, the analytical instrument (Autosorb iQ Station 1), the adsorbate is nitrogen, and the adsorbate is 4.353m 2 / mL, the sample was dried at 120℃ for 3h before testing, the test Bath temperature was 77.35K, Non-ideality: 6.58e-05 1 / Torr, Celltype: 9mm w / o rod.
[0039] It should be noted that the bulk density of the roasted mixture of the present invention is determined by GB / T 1479.1-2011. In the present invention, when testing the bulk density, the mesh number of the roasted mixture is -100 mesh, accounting for 80%.
[0040] In the roasting mixture, in addition to the initial morphology of the lithium-containing ore material itself, the mixing process after adding the roasting aid will also affect the specific surface area and loose density of the overall roasting mixture. As mentioned above, the two physical parameters have a crucial influence on the selective lithium extraction effect when the product is finally used. If the specific surface area of the roasting mixture is too large, or the loose density is small, it may indicate that the degree of dispersion of the roasting aid is low, resulting in large local gaps between the particles of the roasting mixture, and a uniform phase change cannot be achieved during the roasting process; and if the specific surface area is too small, or the loose density is large, it means that the particles between the roasting mixture are densely packed, which will lead to too high uniformity of each phase, resulting in low selectivity of lithium elements and soluble impurities during leaching. After screening by the inventors, when the lithium-containing ore material and the roasting aid are mixed and processed (including grinding, mixing, etc.) to form a roasting mixture, the above-mentioned preferred specific surface area and loose density are most suitable.
[0041] Preferably, the average pore radius of the calcined mixture is 8 to 12 nm.
[0042] It should be noted that the average pore radius of the calcined mixture of the present invention is also determined by the multi-point BET method under the above-mentioned conditions, and can be directly obtained by instrument detection.
[0043] During the preparation of the roasting mixture, the processing and mixing methods have a relatively small impact on the average pore radius of the product. However, the inventors have found through experiments that when the specific surface area and loose density of the roasting mixture are within the range of the relationship described in the present invention, if the average pore radius is maintained within this range, the lithium leaching rate during the second-stage lithium extraction is higher. The inventors speculate that the reason may be that the difference in pore size of the roasting mixture may have a certain impact on the morphology and structure of the insoluble lithium composite phase, and therefore the lithium extraction effect during the second-stage lithium extraction is different.
[0044] Preferably, the roasted mixture satisfies the following relationship:
[0045] 0.0600≤m(Li)·B / [m(Si)·b+m(Al)]≤0.0670.
[0046] When the element composition ratio of the roasted mixture is certain, it can effectively ensure that the lithium leaching rate of the product after roasting can reach more than 80%, and at the same time, the leaching rate of soluble impurity ions in the leachate can be effectively maintained at less than 20%. After further screening, it was found that when the relationship formula of the roasted mixture satisfies the above-mentioned preferred range, the leaching rate of soluble impurity ions in the product during the first lithium extraction is further reduced, and when the filter residue is subjected to the second-stage lithium extraction, the leaching rate of soluble impurities can be reduced to a lower level, the impurity removal cost is lower, and for samples with the same properties, the error of the lithium extraction effect obtained after multiple lithium extractions does not exceed 2%, which is more conducive to the lithium extraction production line of large-volume raw materials.
[0047] Preferably, the roasted mixture further comprises the following components in percentage by mass: S 4-7%.
[0048] In lithium-containing ore materials, especially the more common lithium mica, the sulfur content is relatively low, so sulfur is mostly introduced in the form of anions in the roasting aid salt. Therefore, when the ratios of several key elements in the roasting aid are relatively fixed, the sulfur content is also relatively fixed. In terms of roasting effect, the mass percentage of S in the roasting mixture is best when it is within the above preferred range.
[0049] More preferably, the calcined mixture further comprises the following components in percentage by mass: 0.1-0.3% Mg, 0.5-1% rubidium, 0.1-0.2% cesium, and 0.2-0.4% iron.
[0050] Another object of the present invention is to provide a method for preparing the calcined mixture, comprising the following steps:
[0051] The lithium-containing raw ore material and the roasting aid are mixed according to a predetermined element ratio range, and then processed and mixed to obtain the roasting mixture.
[0052] Preferably, the lithium-containing raw ore material is subjected to elemental analysis before preparing the roasting mixture.
[0053] Compared with the prior art which adopts a mass ratio to simply mix lithium-containing raw ore materials and roasting aids to prepare a mixture before roasting, the roasting mixture of the present invention is particular about the ratio of each elemental component in the mixed powder, and at the same time, the specific surface area and loose density of the mixed powder are made to meet the range requirements of the above relationship through processing means. Without introducing special equipment or processing technology, the roasting mixture can achieve high selective lithium extraction performance after conventional roasting and activation. When the technical personnel in this field are producing lithium extraction from large-volume lithium-containing raw ore materials, they only need to perform elemental analysis on them, prepare corresponding roasting aids according to the results, and then adopt specific processing means according to the conditions of different mixed powders to make them finally meet the physical property requirements. The overall process has almost no cost increase compared with the existing process.
[0054] Another object of the present invention is to provide application of the calcined mixed material in industrial lithium extraction.
[0055] Preferably, the industrial lithium extraction comprises the steps of roasting, crushing, primary lithium leaching, secondary lithium leaching, impurity removal and concentration.
[0056] More preferably, the calcination process comprises the following steps:
[0057] calcining the roasting mixture in a roasting device;
[0058] More preferably, the roasting device is at least one of a rotary kiln, a tunnel kiln, a roller kiln, and a vertical kiln.
[0059] More preferably, the calcination process comprises the following steps:
[0060] The roasted mixture is placed in a rotary kiln and calcined at 550-650°C for 1.5-2.5 hours. During the calcination, the gas is exhausted to remove fluorine. The temperature is then raised to 1100-1110°C and calcined at a rotary kiln rotation speed of 2.5-3.5 r / min for 3.5-4.5 hours.
[0061] More preferably, the roasted mixture is in powder form or is prepared into a spherical shape using a mold before being placed in the rotary kiln, and the diameter of the spherical roasted mixture is 5 to 20 mm.
[0062] More preferably, the heating rate during calcination is 3 to 3.5° C. / min.
[0063] More preferably, the calcination process comprises the following steps:
[0064] The roasted mixture is pressed into blocks of designed size and placed in a roller kiln for calcination at 800-1100°C for 5.5-6.5 hours.
[0065] More preferably, the calcined mixture is pressed into a block with a length of 450 to 550 mm, a width of 400 to 450 mm, and a thickness of 40 to 50 mm.
[0066] More preferably, the heating rate during calcination is 3 to 3.5° C. / min.
[0067] More preferably, the calcination process comprises the following steps:
[0068] The calcined mixture is then pressed into blocks of designed size and calcined in a tunnel kiln at 800-1100°C for 5.5-6.5 hours.
[0069] More preferably, the calcined mixture is pressed into a block with a length of 200 to 300 mm, a width of 50 to 150 mm, and a thickness of 40 to 60 mm.
[0070] More preferably, the heating rate during calcination is 3-3.5°C / min.
[0071] More preferably, the calcination process comprises the following steps:
[0072] The roasted mixture is pressed into balls of designed size and placed in a tunnel kiln for calcination at 800-1100°C for 5.5-6.5 hours.
[0073] More preferably, the calcined mixture is pressed into a spherical shape, and the diameter of the spherical calcined mixture is 30 to 35 mm.
[0074] More preferably, the heating rate during calcination is 3 to 3.5° C. / min.
[0075] It should be noted that, in addition to the above-mentioned roasting method, the roasted mixture of the present invention can also be carried out using other roasting devices or roasting processes, as long as the prepared product can be applied to the subsequent lithium extraction process.
[0076] More preferably, the steps of industrial lithium extraction are:
[0077] (1) adding the calcined mixture into a ball mill after calcination, adding an appropriate amount of lithium-containing washing water to grind into slurry, then adjusting the slurry pH to 6.5-7.5 and controlling the slurry liquid-solid ratio to (2-1.5):1, and after the lithium is completely leached, separating the solid and the liquid to obtain a filter residue and a primary lithium leaching solution;
[0078] (2) After removing impurities from the primary lithium leaching solution, the solution is concentrated and lithium is extracted, thus completing the primary lithium leaching;
[0079] (3) soaking the filter residue obtained in step (1) in water, then adding concentrated sulfuric acid and mixing until the pH value of the obtained mixed solution is 2-3, thereby obtaining a secondary lithium leaching solution;
[0080] (4) After the secondary lithium leaching solution is impurity-removed, it is concentrated and lithium is precipitated, thus completing the secondary lithium leaching.
[0081] More preferably, the liquid-to-solid ratio of the filter residue when soaked in water is (1.4-1.6):1.
[0082] More preferably, the concentrated sulfuric acid is a concentrated sulfuric acid solution with a concentration of 98%.
[0083] The beneficial effect of the present invention is that the present invention provides a roasting mixture and its application. The roasting mixture of the present invention is based on the relationship between the target element lithium to be extracted and the large content of aluminum and silicon elements and the physical property characteristics contained in the mineral-containing raw materials, and at the same time limits the content ratio of the roasting auxiliary elements in the mixture, so that the product has considerable lithium leaching efficiency when leached after roasting, and the degree of precipitation of impurity ions is low. Most importantly, the roasting material prepared by the product has high overall leached lithium ion selectivity after a first leaching and the obtained filter residue is leached for a second time, which is very suitable for deep lithium extraction operations of large quantities of mineral-containing raw materials. DETAILED DESCRIPTION
[0084] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents, raw materials and instruments designed for the implementation of the present invention and comparative examples are all commonly used ordinary reagents, raw materials and instruments unless otherwise specified.
[0085] It should be noted that in the statistics of the components of the lithium-containing ores described in the embodiments and comparative examples of the present invention, some elements actually exist in various forms such as salts, oxides, and complexes (for example, Li, mainly Li2O, but also contains a small amount of lithium salts or lithium-containing composite oxides), but for the convenience of actual statistics and verification, statistics are made in the form of the mass of oxides, for example, Li is calculated in the form of Li2O, Si is calculated in the form of SiO2, and Al is calculated in the form of Al2O3. At the same time, unless otherwise specified, the physical properties of each roasted mixture are measured using the method mentioned above in this article, and the final result is determined by taking the average value of three measurements during the measurement.
[0086] In each embodiment and comparative example, in addition to the main components, some trace elements are actually present in the lithium-containing ore material (especially lithium-containing ore such as lithium mica). For example, in the lithium-containing ore material, in addition to the listed components, the remaining mass is trace elements such as Pb, Cr, Cd, As, P, etc. Since the content of such trace elements is extremely low (the total content does not exceed 2%) and the freeness is high relative to other components, it has basically no effect on the processing and performance of the roasted mixture described in the present invention, and therefore they are not listed one by one in the specific implementation manner below.
[0087] In this specific implementation, the grinding involved is carried out using a commercial stirring mill, the normal stirring grinding rate is (30r / min), and the ball milling is carried out using a commercial vertical ball mill, and the specific ball milling parameters are set in real time.
[0088] In this specific implementation, the raw ore materials involved include:
[0089] (1) Lithium-containing raw ore material 1, lithium mica flotation ore powder from a ore dressing plant in Jiangxi, the composition is shown in Table 1:
[0090] Table 1
[0091]
[0092] (2) Lithium-containing raw ore material 2, lithium mica flotation ore powder from a ore dressing plant in Jiangxi, the composition is shown in Table 2:
[0093] Table 2
[0094]
[0095] (2) Lithium-containing raw ore material 3, lithium mica flotation ore powder from a ore dressing plant in Jiangxi, the composition is shown in Table 3:
[0096] Table 3
[0097] <![CDATA[Li2O]]> K Na Ca Mg Rb、Cs、Fe <![CDATA[Cl - ]]> <![CDATA[SO4 2- ]]> <![CDATA[SiO2]]> F <![CDATA[Al2O3]]> 2.46 9.12 0.26 1.34 0.4 0.77 0.0001 0.05 48 3.12 34.4
[0098] (4) Lithium-containing raw ore material 4, raw ore material mixed with spodumene raw ore and lithium-containing ore waste collected from a mine in Jiangxi, the composition is shown in Table 4:
[0099] Table 4
[0100] <![CDATA[Li2O]]> K Na Ca Mg Rb、Cs、Fe <![CDATA[Cl - ]]> <![CDATA[SO4 2- ]]> <![CDATA[SiO2]]> F <![CDATA[Al2O3]]> 2.30 9.05 0.25 1.35 0.56 2.0 0.0001 0.05 47.5 9.21 26.15
[0101] Example 1
[0102] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0103] The lithium-containing raw ore material 1 and the roasting aids calcium sulfate and sodium sulfate were mixed in a mass ratio of 100:25:15, and then the powder was stirred and ground for 30 minutes and ball-milled at 150 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture, and the elemental composition and physical properties of the roasted mixture were tested. The actual detected elemental composition shall prevail. The elemental composition and physical property parameters of the roasted mixture are shown in Table 5, and X=m(Li)·B / [m(Si)·b+m(Al)] is calculated.
[0104] Example 2
[0105] An embodiment of the roasting mixture and its application described in the present invention is different from Example 1 only in that different materials are added to the roasting mixture during batching, and sodium sulfate is replaced by potassium sulfate of equal mass, resulting in different elemental composition and / or physical property parameters.
[0106] Example 3
[0107] An embodiment of the roasting mixture and its application described in the present invention differs from Embodiment 1 only in that different materials are added to the roasting mixture during batching, and sodium sulfate is replaced by a mixture of equal masses of potassium sulfate and sodium sulfate in a mass ratio of 1:1, resulting in different elemental composition and / or physical property parameters.
[0108] Example 4
[0109] An embodiment of the roasting mixture and its application described in the present invention is different from Example 1 only in that different materials are added to the roasting mixture during batching, and calcium sulfate is replaced by an equal mass of barium sulfate, resulting in different elemental composition and / or physical property parameters.
[0110] Example 5
[0111] An embodiment of the roasting mixture and its application described in the present invention differs from Embodiment 1 only in that different materials are added to the roasting mixture during batching, and calcium sulfate is replaced by a mixture of equal masses of calcium sulfate, strontium sulfate, and barium sulfate in a mass ratio of 2:2:1, resulting in different elemental composition and / or physical property parameters.
[0112] Example 6
[0113] An embodiment of the roasting mixture and its application described in the present invention differs from Embodiment 1 only in that different materials are added to the roasting mixture during batching, and calcium sulfate is replaced by a mixture of equal masses of calcium sulfate, strontium sulfate, and barium sulfate in a mass ratio of 10:7.5:7.5, resulting in different elemental composition and / or physical property parameters.
[0114] Table 5
[0115]
[0116] Example 7
[0117] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0118] The lithium-containing raw ore material 2 and the roasting aids calcium sulfate and sodium sulfate were mixed in a mass ratio of 100:25:15, and then the powder was stirred and ground for 40 minutes and ball-milled at 120 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture. The elemental composition and physical properties of the roasted mixture were tested, and the actual detected elemental composition was used as the basis. The elemental composition and physical property parameters of the roasted mixture are shown in Table 6, and X=m(Li)·B / [m(Si)·b+m(Al)] was calculated.
[0119] Example 8
[0120] The lithium-containing raw ore material 2 and the roasting aids calcium sulfate and potassium sulfate were mixed in a mass ratio of 100:25:13, and then the powder was stirred and ground for 40 minutes and ball-milled at 120 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture. The elemental composition and physical properties of the mixture were tested. The results showed that the error between the result calculated according to the raw material ratio and the actual detected elemental composition ratio was within the effective range. Therefore, the actual detected elemental composition shall prevail. The elemental composition and physical property parameters of the roasted mixture are shown in Table 6, and X=m(Li)·B / [m(Si)·b+m(Al)] is statistically analyzed.
[0121] Example 9
[0122] An embodiment of the roasting mixture and its application described in the present invention is different from Example 7 only in that different materials are added to the roasting mixture during batching, and calcium sulfate is replaced by an equal mass of barium sulfate, resulting in different elemental composition and / or physical property parameters.
[0123] Example 10
[0124] An embodiment of the calcined mixture and its application described in the present invention is different from Example 7 only in that the parameter adjustment during stirring grinding and ball milling is different (grinding for 40 minutes, ball milling at 150 r / min for 1 hour), resulting in different physical properties of the obtained calcined mixture.
[0125] Embodiment 11
[0126] An embodiment of the calcined mixture and its application described in the present invention is different from Example 7 only in that the parameter adjustment during stirring grinding and ball milling is different (grinding for 30 minutes, ball milling at 100 r / min for 1 hour), resulting in different physical properties of the obtained calcined mixture.
[0127] Example 12
[0128] An embodiment of the roasted mixed material and its application according to the present invention comprises the following preparation methods:
[0129] The lithium-containing raw ore material 2 and the roasting aids calcium sulfate and potassium sulfate are mixed in a mass ratio of 106:25:9, and then the powder is first stirred and ground for 40 minutes and ball-milled at 120 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0130] Embodiment 13
[0131] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0132] The lithium-containing raw ore material 2 and the roasting aids calcium sulfate and potassium sulfate are mixed in a mass ratio of 100:30:10, and then the powder is first stirred and ground for 40 minutes and ball-milled at 120 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0133] Embodiment 14
[0134] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0135] The lithium-containing raw ore material 2 and the roasting aids strontium sulfate and sodium sulfate are mixed according to a mass ratio of 100:22:18, and then the powder is first stirred and ground for 40 minutes and ball-milled at 120r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0136] Table 6
[0137]
[0138]
[0139] Embodiment 15
[0140] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0141] The lithium-containing raw ore material 3 and the roasting aids calcium sulfate and sodium sulfate were mixed in a mass ratio of 100:25:15, and then the powder was stirred and ground for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture. The elemental composition and physical properties of the mixture were tested. The results showed that the error between the result calculated according to the raw material ratio and the actual detected elemental composition ratio was within the effective range. Therefore, the actual detected elemental composition shall prevail. The elemental composition and physical property parameters of the roasted mixture are shown in Table 7, and X=m(Li)·B / [m(Si)·b+m(Al)] is statistically calculated.
[0142] Example 16
[0143] An embodiment of the roasted mixed material and its application according to the present invention comprises the following preparation methods:
[0144] The lithium-containing raw ore material 3 and the roasting aids calcium sulfate and sodium sulfate are mixed in a mass ratio of 95:25:15, and then the powder is stirred and ground for 1 hour, and then mixed in a dry mixer to obtain the roasting mixture.
[0145] Examples 17 to 20
[0146] An embodiment of the calcined mixture and its application described in the present invention is different from Example 15 only in that the grinding time is 30 minutes, 45 minutes, 50 minutes and 70 minutes respectively, resulting in different physical properties of the obtained calcined mixture.
[0147] Table 7
[0148]
[0149]
[0150] Embodiment 21
[0151] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0152] The lithium-containing raw ore material 4 and the roasting aids calcium sulfate and sodium sulfate were mixed in a mass ratio of 100:25:15, and then the powder was ball-milled at 120 r / min for 1 h, and then mixed in a dry mixer to obtain the roasted mixture. The elemental composition and physical properties of the roasted mixture were tested, and the actual detected elemental composition was used as the basis. The elemental composition and physical property parameters of the roasted mixture are shown in Table 8, and X=m(Li)·B / [m(Si)·b+m(Al)] was calculated.
[0153] Embodiment 22
[0154] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0155] The lithium-containing raw ore material 4 and the roasting aids calcium sulfate and sodium sulfate are mixed in a mass ratio of 110:25:15, and then the powder is first ball-milled at 120 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0156] Embodiments 23 to 25
[0157] An embodiment of the calcined mixture and its application described in the present invention differs from Example 21 only in that the parameter adjustment during ball milling is different (the rates are 100r / min, 80r / min and 140r / min respectively), resulting in different physical properties of the obtained calcined mixture.
[0158] Embodiment 26
[0159] An embodiment of the roasted mixed material and its application according to the present invention is that the roasted mixed material is prepared according to the following method:
[0160] The lithium-containing raw ore material 4 and the roasting aids barium sulfate and sodium sulfate were mixed in a mass ratio of 100:25:15, and then the powder was ball-milled at 120 r / min for 1 h, and then mixed in a dry mixer to obtain the roasted mixture. The elemental composition and physical properties of the roasted mixture were tested, and the actual detected elemental composition was used as the basis. The elemental composition and physical property parameters of the roasted mixture are shown in Table 8, and X=m(Li)·B / [m(Si)·b+m(Al)] was calculated.
[0161] Table 8
[0162]
[0163] Comparative Examples 1-2
[0164] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0165] The lithium-containing raw ore material 1 and the roasting aids calcium sulfate and sodium sulfate are mixed in a mass ratio of 100:25:15, and then the powders are stirred and ground for 45 minutes and ball-milled at 150 r / min for 80 minutes (Comparative Example 1), and stirred and ground for 15 minutes and ball-milled at 120 r / min for 45 minutes (Comparative Example 2), and then mixed in a dry mixer to obtain the roasted mixture.
[0166] Comparative Example 3
[0167] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0168] The lithium-containing raw ore material 1 and the roasting aids calcium sulfate and potassium sulfate are mixed in a mass ratio of 100:20:20, and then the powder is first stirred and ground for 30 minutes and ball-milled at 150 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0169] Comparative Example 4
[0170] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0171] The lithium-containing raw ore material 1 and the roasting aids barium sulfate and sodium sulfate are mixed in a mass ratio of 100:30:10, and then the powder is first stirred and ground for 30 minutes and ball-milled at 150 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0172] Table 9
[0173]
[0174]
[0175] Comparative Example 5
[0176] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0177] The lithium-containing raw ore material 2 and the roasting aids calcium sulfate and potassium sulfate are mixed in a mass ratio of 100:25:15, and then the powder is first stirred and ground for 40 minutes and ball-milled at 120 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0178] Comparative Example 6
[0179] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0180] The lithium-containing raw ore material 2 and the roasting aids calcium sulfate and sodium sulfate are mixed in a mass ratio of 100:22:18, and then the powder is first stirred and ground for 40 minutes and ball-milled at 120 r / min for 1 hour, and then mixed in a dry mixer to obtain the roasted mixture.
[0181] Comparative Examples 7 to 8
[0182] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0183] The lithium-containing ore material 2 and the roasting aids calcium sulfate and sodium sulfate are mixed in a mass ratio of 100:25:15, and then the powders are first stirred and ground for 40 minutes and ball-milled at 150 r / min for 1 hour (Comparative Example 7), and stirred and ground for 20 minutes and ball-milled at 80 r / min for 1 hour (Comparative Example 8), and then mixed in a dry mixer to obtain the roasted mixture.
[0184] Table 10
[0185]
[0186]
[0187] Comparative Examples 9 to 10
[0188] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0189] The lithium-containing raw ore material 3 and the roasting aids calcium sulfate and sodium sulfate are mixed in a mass ratio of 100:25:15, and then the powders are stirred and ground for 20 minutes (Comparative Example 9), and stirred and ground for 30 minutes and ball-milled at 100 r / min for 20 minutes (Comparative Example 10), and then mixed in a dry mixer to obtain the roasted mixture.
[0190] Comparative Examples 11-12
[0191] A roasted mixed material and application thereof, wherein the roasted mixed material is prepared according to the following method:
[0192] The lithium-containing ore material 4 and the roasting aids calcium sulfate and sodium sulfate are mixed in a mass ratio of 100:25:15, and then the powders are ball-milled at 60 r / min for 40 min (Comparative Example 11) and 150 r / min for 1 h (Comparative Example 12), and then mixed in a dry mixer until the specific surface area and loose density of the obtained mixed powder meet the predetermined requirements, thereby obtaining the roasted mixture.
[0193] Table 11
[0194]
[0195]
[0196] Effect Example 1
[0197] In order to verify the application effect of the roasted mixed material of the present invention, the products of each embodiment and comparative example were then pressed into a block material of 510 mm×430 mm×45 mm, placed in a roller kiln, calcined at 900° C. for 6 h, crushed into a roasted material powder of -100 mesh accounting for 80%, and the powder was added to deionized water to prepare a slurry, and then sulfuric acid and lime powder were used to control the pH of the slurry to 7, at which time the liquid-to-solid ratio of the slurry was 1.5:1, and the reaction was fully stirred for 2 h, and after the lithium was completely leached, the mixture was filtered to obtain a primary lithium leaching solution and a primary filter residue;
[0198] The primary lithium leaching solution is cleaned of impurities and then lithium precipitation is carried out using a lithium precipitation agent.
[0199] Subsequently, the primary filter residue is added with water at a liquid-to-solid ratio of 1.5:1 and mixed and stirred, and then concentrated sulfuric acid is added and mixed until the pH value of the mixed solution stabilizes at 2-3. After the secondary filter residue is sieved, the secondary lithium leaching solution is decontaminated, and then lithium precipitation is carried out using a lithium precipitating agent to complete the secondary lithium extraction.
[0200] The lithium ion leaching rate and soluble impurities (mainly K + 、Na + , Rb + , Cs 2+ 、SO4 2- ), wherein the primary lithium ion leaching rate is obtained by quantitatively calculating the mass of the dry weight roasted material and the mass of the lithium ions in the dry weight primary filter residue using the element quantitative method, and the mass of the leached lithium ions is obtained by the difference, primary lithium ion leaching rate = mass of leached lithium ions / dry weight of lithium ions in the roasted material × 100%, and then the mass of the remaining leached ions is calculated by the difference between the mass of the dry weight roasted material and the primary filter residue and the mass of the leached lithium ions, that is, the mass of the leached soluble impurities, primary soluble impurity leaching rate = mass of leached soluble impurities / dry weight of roasted material × 100%.
[0201] Similarly, the secondary lithium ion leaching rate is obtained by quantifying the mass of the dry weight of the primary filter residue and the mass of the lithium ions in the dry weight of the secondary filter residue using the elemental quantitative method to obtain the mass of the leached lithium ions. Secondary lithium ion leaching rate = mass of leached lithium ions / dry weight of lithium ions in the primary filter residue × 100%. Subsequently, the mass of the remaining leached ions is calculated by the difference between the mass difference of the dry weight of the primary filter residue and the secondary filter residue and the mass of the leached lithium ions, which is the mass of the leached soluble impurities. Secondary soluble impurity leaching rate = mass of leached soluble impurities / dry weight of the primary filter residue × 100%.
[0202] Table 12
[0203]
[0204]
[0205] Effect Example 2
[0206] Further, in order to verify that the calcined mixture described in the present invention has no specificity for the processing conditions when calcining to prepare the calcined material, the products of each embodiment and the comparative example were subsequently pressed into a block material of 245mm×90mm×50mm, placed in a tunnel kiln, calcined at 900°C for 6h, and crushed into a calcined material powder of -100 mesh accounting for 80%, and then the first and second lithium extractions were carried out according to the same method as in Example 1. The results are shown in Table 13.
[0207] Table 13
[0208]
[0209]
[0210]
[0211] It can be seen from the table that the lithium extraction performance of the products of various embodiments after calcination and activation in the tunnel kiln and the roller kiln is similar, indicating that the calcined mixture of the present invention is not limited to being applied in only one calcination condition.
[0212] In addition, the products of Example 1 and Comparative Examples 1 to 4 were pressed into spheres with a diameter of 26 mm, placed in a rotary kiln and calcined at 500°C for 2 hours. During the calcination, the air was evacuated to remove fluorine. The temperature was then raised to 1100°C and calcined at a rotary kiln rotation rate of 3 r / min for 4 hours. The prepared calcined materials were subjected to primary and secondary lithium extraction using the same method. The results are shown in Table 14.
[0213] Table 14
[0214]
[0215] It can be seen that after roasting in a rotary kiln, the product of Example 1 which meets the requirements of the present invention has better lithium extraction performance than the products of Comparative Examples 1 to 4 prepared using the same lithium-containing ore material, and the performance gap is similar to that in Tables 12 and 13.
[0216] In addition, the products of Example 1 and Comparative Examples 1 to 4 were pressed into pellets with a diameter of 30 mm, placed in a vertical kiln, calcined at 1050°C for 6 h, and crushed into -100 mesh powder accounting for 80%. The prepared calcined materials were subjected to primary and secondary lithium extraction using the same method. The results are shown in Table 15. It can be seen that the calcined mixture of the present invention also shows good selectivity for lithium extraction after calcination in the vertical kiln, which can effectively reduce the loss caused by leaching impurities in the lithium extraction industry.
[0217] Table 15
[0218]
[0219] At the same time, another 9 pellets prepared in the same batch as prepared in Example 1 were taken for the same treatment, and the results were statistically analyzed. It was found that the maximum leaching rate of primary soluble impurities was 16.27%, the minimum was 15.24%, and the deviation was no more than 2%; the maximum leaching rate of secondary soluble impurities was 3.47%, the minimum was 3.05%, and the deviation was no more than 0.5%, indicating that when the roasted material prepared by the roasting mixture of the present invention is used for lithium extraction, the selective leaching deviation rate of soluble impurities is low, and the impurity removal preparation for lithium extraction of large quantities of roasted materials can be carried out according to the lithium extraction results of a small number of pre-treated batch samples.
[0220] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A roasted mixed material for industrial lithium extraction, characterized in that: Includes the following ingredients: One, two or three of Ca, Sr and Ba, and one or both of Na and K; The mass percentage of Ca, Sr and Ba in the roasting mixture satisfies: 5%≤Ca+Sr+Ba≤11%; The mass percentage of Na and K in the roasting mixture satisfies: 10%≤Na+K≤12%; The components of the calcined mixture also include Li, Si and Al, and satisfy the following relationship: 0.0550≤m(Li)·B / [m(Si)·b+m(Al)]≤0.0680; Where m(Li) is the mass percentage of Li in the calcined mixture; m(Si) is the mass percentage of Si in the calcined mixture; m (Al) is the mass percentage of Al in the roasted mixture; B is the specific surface area of the roasted mixture, in m 2 / g; b is the bulk density of the roasted mixture, in g / cm 3 ; The specific surface area of the calcined mixture is 1.8 to 2.5 m 2 / g, bulk density is 0.6~1 g / cm 3 .
2. The roasting mixture according to claim 1, characterized in that The composition of the calcined mixture includes the following mass percentages of Li, Si and Al: 0.5-2% of Li, 16-20% of Si, and 10-12% of Al.
3. The roasting mixture according to claim 1, characterized in that The mass percentage of Ca, Sr and Ba in the roasting mixture satisfies: 5%≤Ca+Sr+Ba≤7.6%; The mass percentage of Na in the roasting mixture is 0.1-4%; The mass percentage of K in the roasting mixture is 6-11.5%.
4. The roasting mixture according to claim 1, characterized in that The average pore radius of the calcined mixture is 8-12 nm.
5. The roasting mixture according to claim 1, characterized in that The roasted mixture satisfies the following relationship: 0.0600≤m(Li)·B / [m(Si)·b+m(Al)]≤0.0670.
6. The roasting mixture according to claim 1, characterized in that The roasting mixture also includes the following components in percentage by weight: S 4-7%.
7. A method for preparing a roasted mixed material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The lithium-containing raw ore material and the roasting aid are mixed according to the element ratio range, and then processed and mixed to obtain the roasting mixture.
8. Use of the calcined mixed material according to any one of claims 1 to 6 in industrial lithium extraction.
9. The use according to claim 8, characterized in that The industrial lithium extraction comprises the steps of roasting, crushing, primary lithium leaching, secondary lithium leaching, impurity removal and concentration treatment.
10. The use according to claim 9, characterized in that The calcination process comprises the following steps: The roasting mixture is calcined in a roasting device; the roasting device is at least one of a rotary kiln, a tunnel kiln, a roller kiln, and a vertical kiln.
11. The use according to claim 10, characterized in that The calcination process comprises the following steps: The roasted mixture is placed in a rotary kiln and calcined at 550-650°C for 1.5-2.5 hours. During the calcination, the gas is evacuated to remove fluorine. The temperature is then raised to 1100-1110°C and calcined at a rotary kiln rotation speed of 2.5-3.5 r / min for 3.5-4.5 hours.
12. The use according to claim 11, characterized in that The roasted mixture is in powder form or is prepared into a spherical shape by a mold before being placed in the rotary kiln, and the diameter of the spherical roasted mixture is 5-20 mm.
13. The use according to claim 10, characterized in that The calcination process comprises the following steps: The roasted mixture is pressed into blocks of designed size and placed in a roller kiln for calcination at 800-1100°C for 5.5-6.5 hours.
14. The use according to claim 13, characterized in that The roasted mixed material is pressed into a block with a length of 450-550 mm, a width of 400-450 mm, and a thickness of 40-50 mm.
15. The use according to claim 9, characterized in that The calcination process comprises the following steps: The calcined mixture is then pressed into blocks of designed size and calcined in a tunnel kiln at 800-1100°C for 5.5-6.5 hours.
16. The use according to claim 15, characterized in that The calcined mixed material is pressed into a block with a length of 200-300 mm, a width of 50-150 mm, and a thickness of 40-60 mm.
17. The use according to claim 10, characterized in that The calcination process comprises the following steps: The roasted mixture is pressed into balls of designed size and placed in a tunnel kiln for calcination at 800-1100°C for 5.5-6.5 hours.
18. The use according to claim 17, characterized in that The roasted mixture is pressed into a spherical shape, and the diameter of the spherical roasted mixture is 30-35 mm.
Citation Information
Patent Citations
Method for extracting lithium from electrolytic aluminum waste residues through mixed salt calcination method
CN115216645A